Mucosa-associated bacteria in two middle-aged women diagnosed with collagenous colitis - Gustafsson, Rita J (Baishideng Publishing Group Co., Limited, 2012)
AIM: To characterize the colon microbiota in two women histologically diagnosed with collagenous colitis using a culture-independent method. METHODS: Biopsies were taken from the ascending colon and the total DNA was extracted. Universal bacterial primers were used to amplify the bacterial 16S rRNA genes. The amplicons were then cloned into competent Escherichia coli cells. The clones were sequenced and identified by comparison to known sequences. RESULTS: The clones could be divided into 44 different phylotypes. The microbiota was dominated by Firmicutes and Bacteroidetes. Seven phylotypes were found in both patients and constituted 47.5% of the total number of clones. Of these, the most dominating were clones similar to Bacteroides cellulosilyticus, Bacteroides caccae, Bacteroides thetaiotaomicron, Bacteroides uniformis and Bacteroides dorei within Bacteroidetes. Sequences similar to Faecalibacterium prausnitzii and Clostridium citroniae were also found in both patients. CONCLUSION: A predominance of potentially pathogenic Bacteroides spp., and the presence of clones showing similarity to Clostridium clostridioforme were found but the overall colon microbiota showed similarities to a healthy one. Etiologies for collagenous colitis other than an adverse bacterial flora must also be considered.